Negociação e emoção: um estudo em vendas de projetos de consultoria e auditoria - Vantine, Juliana Martins (2010)
This dissertation is related to emotions and gender in the sales negotiation process of consulting and audits projects, and the main objective of it is to understand the perception regarding the emotions in the negotiation process, as well as identifies what kind emotions are presented in this process. One of the aspects that get influence into a negotiation process is the emotion, which is presented in any negotiation process. The emotion can be better controlled by a person and more apparent in another; however what is common in this process is the fact that it exists and can be an issue in a big deal closing process. Some emotions can confuse the thoughts complicating the relationship with the counterparty during the negotiation process. Besides the emotions, other variables that can influence the negotiation are as follows: power, time and information. Not necessarily in a negotiation you must have all three variables, as just one of them can occur in this process. These variables come from contact with people; learning regarding prior situations lived by the person, prior experiences; therefore based on the day-by-day activities lived by the person. The survey had a sample size of 30 negotiators, including 11 women and 19 men who work in São Paulo with a global auditing and consulting firm. In order to catch the data the PANAS-X scale was applied, which contains 60 emotions, and are grouped into the following sub-scales: positive emotion, negative emotion, juvenescence, self confidence, attention / care, fear, hostility, guilt, sadness / melancholy shyness, fatigue, serenity and surprise. In addition, interviews were performed using opening questions in order to understand in detail how the negotiation process is. The result was that there are differences in the emotions felt by men and women negotiators, and in this sample the negotiators presented much more positive emotions, such as interested, caring, active, determined, focused, self-assured, and confident